Improving Early Childhood Cognitive Abilities Through Science-Based Learning In RA Nurul Yasin, Mejobo Kudus District - Ismartoyo Ismartoyo; Aini Indriasih; Yuli Haryati; Dian Ratu Ayu Uswatun Hasanah (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The purpose of the study is to test how science learning can measure the congenital development of early childhood. So from these problems, researchers need to know whether the implementation of science-based learning has an effect and can improve early childhood cognitive development in RA Nurul Yasin, Kudus Regency.  The sample of this study was 17 early childhood children in RA Nurul Yasin, Mejobo District, Kudus Regency in 2022. The design of experimental research was explored using activity experiments with observations. The analysis used is the analysis of different tests before and after the experiment.  The results showed that there was an influence of 0. 411 with a sig of 0.128. This indicates an increase in the ability of cognitive abilities after being given treatment.